Description of new species of deep water Sthenolepis Willey, 1905 and Neoleanira Pettibone, 1970 (Annelida, Sigalionidae) from off Northern California, with the redescription of Sthenolepis spargens Fauchald, 1972 - Cruz-Gómez, Christopher; Blake, James A. (Zootaxa, 2024)
Two new species of scale worms belonging to Sigalionidae are described from deep water off Northern California. Specimens were collected as part of long-term monitoring surveys at the San Francisco Deep-Ocean Dredged Material Disposal Site, and baseline studies by the U. S. Navy off Northern California. Specimens were dredged from the continental slope at depths of 2,350 to 3,221 m. Sthenolepis ruffi n. sp. is characterized by having long palps and tentacular cirri, upper neurochaetae group with long blades, and the lowest neurochaetae group with non-canaliculate blades. Due to the morphological and distribution similarities, Sthenolepis spargens from Mazatlán, México is redescribed and compared with the newly described S. ruffi n. sp. Further, Neoleanira solitaria n. sp. stands out among the members of the genus by having a simple fusiform supracicular neurochaeta in posterior segments. Comparative tables of both genera are included. Both new species represent new additions to the knowledge of these genera, more than 50 years after the last description.